Dependência de calibre na equação de Gap de Quarks - Lessa , José Roberto (2020)
In this Master's thesis the quark-gap equation is treated in a functional approach based on the Dyson-Schwinger equations in Quantum Chromodynamics with a focus on local and global symmetries and the breaking thereof. As a first introductory study, mass functions obtained from numerical solutions of the quark gap equation are calculated employing gluon and ghost propagators in R_ gauge from Dyson-Schwinger equations and lattice QCD along with a quark-gluon vertex in the integral kernel that ranges from the leading Rainbow truncation to ans atze for its transverse components constrained by gauge symmetry, i.e. the associated Slavnov-Taylor identities. This will allow for an assessment of the gauge dependence of dynamical chiral symmetry breaking for di_erent quark avors. To this end, we will employ available lattice data for the longitudinal and transverse part of the gluon propagator. This qualitative and quantitative analysis of the quark's mass function is important for future studies of bound states, such as charmed mesons immersed in a nuclear medium and is relevant for the physics programs at the future accelerator of the Facility for Antiproton and Ion Research(FAIR) in Germany.